Effect of Vitamin D3 on Colonization Genes Expression of Haemophilus influenzae Isolated from Children with Otitis Media Associated with Temporomandibular Joint Pain - Motib, Anfal Shakir; Idan, Hayder Mahdi (AL-Kindy College Medical Journal, 2025)
Background: Acute otitis media (AOM) is the middle ear inflammation caused by various microorganisms, including bacteria. Haemophilus influenzae is a common bacterium that causes this inflammatory condition. This study aimed to determine the role of cholecalciferol (D3) in the expression of colonization genes in H. influenzae isolated from children with otitis media, which is associated with temporomandibular joint pain. Subjects and Methods: A total of 160 ear swabs and blood samples were collected from children with recurrent acute otitis media (AOM) for culture and sensitivity tests. The number of patients with pain in the TMJ was recorded, whether by pressure on the joint area or during mouth opening. Vitamin D3 was measured using an Enzyme-Linked Immunosorbent Assay. The minimum inhibitory and bactericidal concentrations of vitamin D3 were identified. Quantitative real-time PCR was used to evaluate the impact of this vitamin on the expression of pilA, hmw1, and hmw2. Results: This study showed that H. influenzae caused 28.12 % of AOM, and this inflammation occurred in 30.6% of children aged 1-2 years. Interestingly, 14.38 % of AOM patients had TMJ pain, while 85.62 % did not. Vitamin D3 levels in AOM patients were lower than those in normal children. The current study demonstrated that the expression of colonization genes in H. influenzae, the most common bacterium causing AOM, is upregulated in the absence of vitamin D3. However, these genes’ expressions are downregulated in the presence of this vitamin. Conclusions: This study demonstrated that vitamin D3 inhibited the colonization gene expression of H. influenzae and altered the expression of these genes, suggesting therapeutic roles in infection prevention.